Understanding the Cash Flow-Fundamental Ratio - Chiou, Chyi-Lun (International Journal of Economics and Financial Issues, 2014)
This article investigates the use of cash flow-fundamental ratio in forecasting stock market return and examines implications behind this ratio. By presuming the dynamics of cash flow-fundamental ratio I identify the relationship between economic uncertainty and risk premium. The evidence shows that cash flow-fundamental ratio is procyclical and is a predictor of cash flow growth and excess returns. The cash flow-fundamental ratio is proved to be negatively associated with risk premium. I also examine that the mean-reversion property of cash flow-fundamental ratio is triggered by profitability. In contrast to the assumption of stationary in stock price, mean reversion in profitability is more reasonable and has been proved by Fama and French (2000). Keywords: Predictability of stock return; Cash flow-fundamental ratio. JEL Classifications: G12